Investigating willingness to communicate (WTC) among polytechnic students - Maizan Binti Mohamad (Global Econedu, 2024)
Learning a second language such as English is a challenging task for many language learners due to various psychological factors such as unwillingness to communicate in the language. Thus, the current study primarily aims to find out levels of willingness to communicate in English (WTC). A quantitative approach was employed whereby data were collected using an instrument which is Willingness to Communicate Scale (WTCS). The questionnaires were administered to 123 diploma students at Politeknik Hulu Terengganu. Using SPSS 22.0, data were analyzed descriptively, namely minimum, maximum, mean, and standard deviation. The findings revealed that students reported having a very low willingness to communicate in the English language. The study provides several pedagogical implications for both ESL students and practitioners. They could potentially guide educators in improving their teaching and learning process by creating a more conducive and stress-free environment to encourage students to communicate willingly. This new environment will hopefully enhance students' performance, especially in using the English language to communicate.